Implementation of Higher Order Thinking Skills In Physical Education Learning In Covid-19 Era: Is It Work? - Festiawan, Rifqi; Khurrohman, Moch Fath (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine how well the implementation of Higher Order Thinking Skills (HOTS) based on Physical Education at Banyumas Regency in 2020. This type of research is a quantitative descriptive study using a survey method. The population in this study were all physical education teachers in Banyumas Regency, totaling 29 teachers, who were taken using the total sampling technique. The data collection technique used a questionnaire. The data analysis technique used percentage descriptive analysis. The results showed that the implementation of Higher Order Thinking Skills (HOTS) based Physical Education at Banyumas Regency in 2020 was in the